β-Defensin 129 Attenuates Bacterial Endotoxin-Induced Inflammation and Intestinal Epithelial Cell Apoptosis - Xie, Kunhong; Xie, Hongmei; Su, Guoqi; Chen, Daiwen; Yu, Bing; Mao, Xiangbing; Huang, Zhiqing; Yu, Jie; Luo, Junqiu; Zheng, Ping; Luo, Yuheng; He, Jun (Frontiers in Immunology, 2019)
Defensins have attracted considerable research interest worldwide because of their potential to serve as a substitute for antibiotics. In this study, we characterized a novel porcine β-defensin (pBD129) and explored its role in alleviating bacterial endotoxin-induced inflammation and intestinal epithelium atrophy. The pBD129 gene was cloned and expressed in Escherichia coli. A recombinant pBD129 protein was also purified. To explore its role in alleviating the endotoxin-induced inflammation, mice, with or without lipopolysaccharide (LPS) challenge were treated by pBD129 at different doses. The recombinant pBD129 showed significant antimicrobial activities against the E. coli and Streptococcus with a minimal inhibitory concentration (MICs) of 32 μg/mL. Hemolytic assays showed that the pBD129 had no detrimental impact on cell viabilities. Interestingly, we found that pBD129 attenuated LPS-induced inflammatory responses by decreasing serum concentrations of inflammatory cytokines, such as the IL-1β, IL-6, and TNF-α (P < 0.05). Moreover, pBD129 elevated the intestinal villus height (P < 0.05) and enhanced the expression and localization of the major tight junction-associated protein ZO-1 in LPS-challenged mice. Additionally, pDB129 at a high dose significantly decreased serum diamine oxidase (DAO) concentration (P < 0.05) and reduced intestinal epithelium cell apoptosis (P < 0.05) in LPS-challenged mice. Importantly, pBD129 elevated the expression level of Bcl-2-associated death promoter (Bcl-2), but down-regulated the expression levels of apoptosis-related genes such as the B-cell lymphoma-2-associated X protein (Bax), BH3-interacting domain death agonist (Bid), cysteinyl aspartate-specific proteinase-3 (Caspase-3), and caspase-9 in the intestinal mucosa (P < 0.05). These results suggested a novel function of the mammalian defensins, and the anti-bacterial and anti-inflammatory properties of pBD129 may allow it a potential substitute for conventionally used antibiotics or drugs.